Ochrona klimatu w czasie pandemii COVID-19 - Pinkas, Aleksandra (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2023)
The SARS-CoV-2 virus pandemic, which has the character of an unpredictable phenomenon, is characterized as increasing global warming, by the highest level of extremes. The pandemic crisis that has changed the functioning of the global economy has not stopped action on climate protection. The scientific consensus on the existence of global warming as an effect caused by unlimited human activity has resulted in international agreements to achieve climate neutrality. The substantiation of the climate targets through the adoption of law creating obligations on the part of the Member States in this regard has taken place during the pandemic. The actions taken for economic recovery from the pandemic crisis are closely integrated with tackling to climate change and adopt to its effects.
Keywords: climate protection; climate neutrality; global warming; SARS-CoV-2 pandemic